Prevalence of adherence and its impact on quality of life in oral anticoagulant users in Egypt: A cross-sectional study from two Egyptian university hospitals - Mohamed Terra; Amro Badr; Mohamed Baklola; Ibrahim Hegazy; Muhammed Elmanzlawey; Islam Elrakhawy; Ahmed Muhammed (BMC Cardiovascular Disorders)
Abstract Background Oral anticoagulant therapy (OAT) is critical for managing thromboembolic disorders, but adherence challenges significantly impact its effectiveness and patients’ quality of life (QoL). This study explores the predictors of adherence and their effects on QoL among OAT users in Egypt. Methods This multi-center cross-sectional descriptive study with an analytical component was conducted at Mansoura University Hospital and Ain Shams University Hospital. Participants were adults over 18 years old, on OAT for at least one month, who provided informed consent. Convenience sampling was used to recruit 212 participants. Data were collected using a survey that included socio-demographic details, the Arabic Version of the Adherence to Refills and Medications Scale (ARMS), and the WHOQOL-BREF questionnaire. Statistical analyses included descriptive statistics, chi-square tests, Student’s t-tests, and multivariate logistic regression. Results The study included 212 participants, with an average age of 55 years, 57% female and 43% male. Among the participants, 25.5% were adherent to their anticoagulant regimen, while 74.5% were non-adherent. Adherence was significantly higher among NOAC users (44.4%) compared to warfarin users (19.0%). Key predictors of adherence included the use of NOACs (OR = 2.7), residency in rural areas (OR = 2.4), and having first-degree relatives in medical specialties (OR = 2.4). Quality of life scores were significantly higher for NOAC users in psychological, social, and environmental domains compared to warfarin users. The overall QoL score was also higher in NOAC users. Poorer adherence was associated with lower scores in these QoL domains. Conclusions Our study indicates that NOACs enhance adherence and quality of life relative to VKAs. Key adherence predictors include NOAC use, rural residency, and having relatives in medical professions. Educational level, initially significant, did not persist as a predictor in multivariate analysis. Targeted strategies are needed to improve adherence and patient outcomes.